Exploring the Content Strategy of @bachrulalam on TikTok for Arabic Learning - Siti Nuraeni; Sofyan Sauri; Tatang (Jurusan Pendidikan Bahasa Arab UIN Kiai Ageng Muhammad Besari onorogo, 2025)
This study aims to analyze the content strategy employed by the TikTok account @bachrulalam__ within the context of Arabic language learning. It utilizes the Four Pillars of Social Media Content Strategy framework developed by Lon Safko and David K. Brake, which includes education, communication, collaboration, and entertainment. A qualitative approach with a descriptive exploratory method was adopted, utilizing primary data sourced from TikTok videos uploaded between 2022 and 2024. Data collection was performed through documentation and note-taking, while data analysis was conducted thematically in accordance with the content strategy framework. The findings indicate that the @bachrulalam__ account consistently delivers Arabic language learning content using an engaging audio-visual format and concise video presentations. The four pillars of the content strategy are implemented in a balanced manner, with a notable emphasis on educational and entertainment components. This approach has been effective in increasing audience engagement with Arabic language learning via TikTok. This study contributes to the existing literature on Arabic language acquisition educational content strategies in social media, particularly TikTok. Additionally, it addresses a research gap concerning the role of local content creators like @bachrulalam__ who employ an edutainment approach to deliver material in an informal yet impactful manner. Abstrak Penelitian ini bertujuan untuk menganalisis strategi konten yang diterapkan oleh akun TikTok @bachrulalam__ dalam konteks pembelajaran bahasa Arab, dengan mengacu pada kerangka Four Pillars of Social Media Content Strategy yang dikembangkan oleh Lon Safko dan David K. Brake, mencakup pilar edukasi, komunikasi, kolaborasi, dan hiburan. Pendekatan yang digunakan adalah kualitatif dengan metode deskriptif eksploratif, dengan sumber data primer berupa video unggahan TikTok pada periode 2022–2024. Teknik pengumpulan data dilakukan melalui dokumentasi dan simak-catat, sedangkan analisis data dilakukan secara tematik berdasarkan kerangka strategi konten tersebut. Hasil penelitian menunjukkan bahwa akun @bachrulalam__ secara konsisten menyajikan konten pembelajaran bahasa Arab dengan pendekatan audio-visual yang menarik serta format video pendek yang mudah dipahami. Keempat pilar strategi konten diterapkan secara proporsional, dengan dominasi pada elemen edukatif dan hiburan. Strategi ini terbukti mampu meningkatkan minat audiens dalam mempelajari bahasa Arab melalui media sosial TikTok. Penelitian ini memberikan kontribusi terhadap pengembangan literatur mengenai strategi konten edukatif pembelajaran bahasa Arab dalam media sosial, khususnyaTikTok. Studi ini juga mengisi kesenjangan riset terkait peran kreator konten lokal seperti @bachrulalam__ yang menggunakan pendekatan edutainment untuk menyampaikan materi secara informal namun efektif.